Gender-responsive budgeting as fiscal innovation: Evidence from India on "processes" - Lekha S. Chakraborty (Levy Economics Institute of Bard College, 2014)
Gender-responsive budgeting (GRB) is a fiscal innovation. Innovation, for the purposes of this paper, is defined as a way of transforming a new concept into tangible processes, resources, and institutional mechanisms in which a benefit meets identified problems. GRB is a fiscal innovation in that it translates gender commitments into fiscal commitments by applying a "gender lens" to the identified processes, resources, and institutional mechanisms, and arrives at a desirable benefit incidence. The theoretical treatment of gender budgeting as a fiscal innovation is not incorporated, as the focus of this paper is broadly on the processes involved. GRB as an innovation has four specific components: knowledge processes and networking, institutional mechanisms, learning processes and building capacities, and public accountability and benefit incidence. The paper analyzes these four components of GRB in the context of India. The National Institute of Public Finance and Policy has been the pioneer of gender budgeting in India, and also played a significant role in institutionalizing gender budgeting within the Ministry of Finance, Government of India, in 2005. The Expert Committee Group on "Classification of Budgetary Transactions" makes recommendations on gender budgeting - Ashok Lahiri Committee recommendations - that will become part of the institutionalization process, integrating the analytical matrices of fiscal data through a gender lens and also the institutional innovations for GRB. Revisiting the 2004 Lahiri recommendations and revamping the process of GRB in India is inevitable, at both ex ante and ex post levels.
Keywords: H8; 330; Gender-responsive Budgeting; Innovation; Institutions